Citizen Cannes the man behind the Cannes Film Festival - Jacob, Gilles 1930- (London Phaidon Press Limited, 2011)
For over thirty years, Gilles Jacob has been the soul of the biggest film festival in the world - the Cannes Festival - of which he was elected President in 2000. As witness and champion of the film industry, Jacob describes in Citizen Cannes his journey from that of a Jewish boy saved by a Catholic seminary during World War II, later becoming an entrepreneur and a film critic, and finally an accomplished man who in 1978 was appointed general delegate of the biggest vanity fair in the world.
"First published in English 2011. ... Published in French by Robert Laffont, 2009. ... Translated by Sarah Robertson"--page[384]
30 years behind the scenes of the world's greatest festival"--Cover.
Includes index.
Keywords: Jacob, Gilles; Film festivals -- France -- Cannes -- History; Motion picture industry; Motion picture producers and directors -- France -- Biography; Motion pictures -- Competitions -- France -- Cannes -- History; Motion picture actors and actresses